KAJIAN KUAT TEKAN DAN INFILTRASI PADA BETON NON PASIR (Study Of Compressive Strength And Infiltration Of no-fines Concrete) - Edi Kurniadi; Lava Himawan (Prodi Teknik Sipil FT Universitas Sebelas Maret, 2019)
No fines concrete can be known such as porous concrete, no-fines concrete and pervious concrete, because not use of sand in the mixture causing the cavities between coarse aggregates. When the rainy season, especially in urban areas there are many flood because the water is difficult to infiltration into the ground. Because permeable nature of non-fines concrete which can accelerate the absorption of water to the soil and to the water channel, reduce run-off and increase groundwater reserves. In this research will study for compressive strength and infiltration in non-finnes concrete. This research uses coarse aggregates from the results of stone crushing machines with coarse aggregate sizes (5-10) mm. cement: aggregate ratio used 1: 2; 1: 3; 1: 4; 1: 5; 1: 6; 1: 7; 1: 8. The study began with material checking, planning of material requirements, making non-sand concrete, then testing compressive strength, and infiltration testing at the age of 28 days. The results showed that the compressive strength of non-finnes concrete with a variation of the ratio of cement : gravel 1: 2 is 33.19 MPa while for a mixture of 1: 8 it is 5.23 MPa. The Infiltration rate has increased along with the greater variation in the ratio of the mixture. The maximum infiltration rate for a mixture of 1: 8 is 9.44 mm/sec. The infiltration rates in no-finnes concrete can be used to accelerate the absorption of water into the soil and can function to reduce water on the surface of the yard.